2005
DOI: 10.1152/ajpgi.00020.2005
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of cyclooxygenase-2 and thromboxane A2production mediate the action of tumor necrosis factor-α in isolated rat myenteric ganglia

Abstract: Intact myenteric ganglia from 4- to 10-day-old rats were isolated from the small intestine. The preparations were cultured overnight, and drugs were applied within this time frame (20 h). Whole cell patch-clamp technique was used to measure basal membrane potential and carbachol-induced depolarization at neurons within these ganglia. Pretreatment with TNF-alpha (100 ng/ml) hyperpolarized the membrane (from -31.0 +/- 2.7 mV under control conditions to -61.2 +/- 3.2 mV in the presence of the cytokine) and potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Because native TXA 2 has only a half‐life of about 30 s in aqueous solutions, 15 all experiments were performed with the stable TXA 2 derivative, cTXA 2 , in which both O‐atoms in the cyclic structure of the molecule are replaced by carbon atoms 16 . In accordance with previous observations, 10 cTXA 2 (10 −6 mol L −1 ) induced a hyperpolarization of the membrane of myenteric neurones from −19.3 ± 2.5 to −29.3 ± 2.3 mV ( n = 9, P < 0.05; Fig. 1A).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Because native TXA 2 has only a half‐life of about 30 s in aqueous solutions, 15 all experiments were performed with the stable TXA 2 derivative, cTXA 2 , in which both O‐atoms in the cyclic structure of the molecule are replaced by carbon atoms 16 . In accordance with previous observations, 10 cTXA 2 (10 −6 mol L −1 ) induced a hyperpolarization of the membrane of myenteric neurones from −19.3 ± 2.5 to −29.3 ± 2.3 mV ( n = 9, P < 0.05; Fig. 1A).…”
Section: Resultssupporting
confidence: 93%
“…This effect was suppressed by nimesulide, a drug acting as specific COX‐2 inhibitor 2 . A subsequent immunhistochemical investigation revealed an upregulation of COX‐2 in the presence of TNF‐ α 10 . The electrophysiological effects of TNF‐ α seem to be mediated by TXA 2 , as suggested by the sensitivity against a TXA 2 receptor blocker (such as Bay u3405) or a TXA 2 synthase inhibitor (such as 1‐benzylimidazole), and by the ability of carbocyclic TXA 2 (cTXA 2 ), a stable TXA 2 derivative, to mimic the actions of the cytokine 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In turn, increased oxidative stress has been shown in hepatic cells lines to increase production of TXB 2 via induction of thromboxane synthase (23). It has been also shown that cytokine-induced COX-2 upregulation is associated with thromboxane release in airway smooth muscle cells, which is blocked by a selective COX-2 inhibitor (34), and that TNF-␣ stimulates production of thromboxane in myenteric neurons by mechanisms involving increased COX-2 and thromboxane synthase activity (48). Thus, although the mechanism(s) of the upregulation of TXB 2 in diabetic mice remain unclear, our data suggest that by modulating myocardial oxidative stress, prostanoid content, and inflammation in response to diabetes, COX-2 gene inactivation may be associated with beneficial effects on cardiovascular function in experimental diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This property of TNF-α could explain the negative impact of cytokines on gut motility. In a molecular point of view, the effect of TNF-α is mediated by an upregulation of the Cyclo-Oxygenase (COX-2), which in turn increases the production of an arachidonic acid derived-molecule, Thromboxane A2 (TXA 2 ) ( Rehn et al, 2005 ). In experimental colitis, Chandrasekharan et al (2013) have also demonstrated that TNF-α has an effect on the apoptosis rate of enteric neurons.…”
Section: How the Inflammation Modulates The Enteric Nervous System?mentioning
confidence: 99%